Implementasi Model Pembelajaran RADEC untuk Mengembangkan Kemampuan Berpikir Kritis di MIN 3 Kebumen - Nabila, Afaf; Nurhidayah, Nurhidayah (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is (1) to determine the preparation stage implementation of the RADEC learning model in developing abilities students critical thinking in science subject VA class at MIN 3 Kebumen (2) to determine the implementation stage of the implementation of the RADEC learning model in developing students critical thinking skills in science subjects VA class at MIN 3 Kebumen (3) to find out the implementation evaluation stage RADEC learning model in developing critical thinking skills students in science subject VA class at MIN 3 Kebumen. This research is a descriptive qualitative research. Students under study are students of class VA MIN 3 Kebumen with a total of 22 students. Which method used in this study is a qualitative method. Data collection the results of interviews, observations and documentation. Then the analysis technique data through data reduction, data presentation, and drawing conclusions. Based on the results of the study it can be concluded that: (1) the preparatory stage the implementation of the RADEC learning model includes a decisive discussion dates, materials, preparing learning resources, making lesson plans and preparing questions (2) the implementation stage of implementing the RADEC learning model in developing students critical thinking skills can increase, seen from critical thinking indicators at each meeting. That the results of meeting 1 on indicators provided simple explanations 31.8%, developed basic skills 27.2%, concluded that students had not been able to demonstrate them, provided further explanations 31.8%, and set strategies and techniques 22.7%. While at meeting 2 there was a change in the indicators giving simple explanations increasing to 36.6%, developing basic skills increasing to 31.8%, concluding increasing to 4.5%, giving further explanations increasing to 31.8%, and setting strategies and technique increased to 31.8% (3) stages evaluation of the implementation of the RADEC learning model in developing students critical thinking skills, namely the teacher always motivates and guiding students so that their critical thinking skills can develop properly